Assessment of testicular self-examination awareness and practice among adult males in Ajman, United Arab Emirates: A cross-sectional study. - Abubakker Siddiq Mohamed Hameed; Mohammed Nayeem Shaji; Prasanna Appiya Premvignesh; Janet Chichu James; Miral Salama; Manda Venkatramana; Liju Susan Mathew; Neema Halfan; Anusha Sreejith; Jayadevan Sreedharan; Jayakumary Muttappallymyalil (PLoS ONE, 2025)
Introduction Testicular cancer (TC) is one of the most common cancers affecting men between the ages of 15 and 40 years. Testicular self-examination (TSE) is an effective tool for the early detection of TC, significantly improving survival rates. This study aimed to assess the level of awareness and practice of TSE among adult males in Ajman, United Arab Emirates (UAE). Methods A descriptive cross-sectional study was conducted among 1031 adult men residing in Ajman, UAE, using a structured self-administered and interviewer-administered questionnaire. Descriptive statistics were used to summarize the data, and Chi-square tests were applied to assess associations between awareness and practice of TSE with socio-demographic variables. Results The mean age of participants was 34.9 ± 9.8 years. Overall, 212 participants (20.6%) reported being aware of TSE. Among those who were aware, 106 individuals (50%) reported practicing TSE. Conclusion The findings highlight a low level of awareness and practice of TSE among men in Ajman. There is a critical need for targeted health campaigns and educational interventions to promote knowledge and practice of TSE. Healthcare providers should play a proactive role in raising awareness about TC and the importance of regular self-examination for early detection.